Implementasi Pembelajaran Bilingual pada Mata Pelajaran Pendidikan Agama Islam dalam Peningkatan Kecakapan Berbahasa Siswa di SMA Negeri 2 Sangatta Utara - Selawat Setiawan; Faelasup; Muhammad (Global Education Journal, 2026)
This study investigated the implementation of a bilingual classroom program within Islamic Education (PAI) subjects at SMAN 2 Sangatta Utara using a descriptive qualitative approach. Data were gathered through passive participant observation, semi-structured in-depth interviews, and document analysis, and then analyzed through an interactive framework. The findings indicated that the program was executed systematically by integrating national curricula with international linguistic goals through code-switching, bilingual slides, and project-based learning. However, several operational barriers emerged, including teachers' limited linguistic competencies, severe shortage of standardized bilingual materials, potential semantic biases in translating sensitive theological concepts, sharp disparities in students' English proficiency, and limited instructional time. To address these challenges, integrated solutions were deployed, encompassing In-House Training (IHT) for teachers, customized scaffolding-based worksheets, standardized mini-dictionaries, differentiated learning strategies, and the flipped classroom model. Additionally, utilizing interactive quiz apps and initiating custom thematic bilingual days successfully reduced cognitive overload and built a supportive ecosystem. In conclusion, the systematic collaboration between teacher capacity building, technological adaptation, and inclusive management successfully sustained the quality of this global competency innovation.